ARCHITECTURE OF BUKHARA MOSQUES DURING THE SHAYBANIDS - Karsiboeva Mavluda Abdullayevna (Journal of Applied Science and Social Science, 2026)
This article examines the formation, development, and distinctive characteristics of mosque architecture in Bukhara during the Shaybanid period. The study highlights the construction activities carried out in sixteenth-century Bukhara, with particular attention to the architectural structure, functional roles, and artistic ornamentation of mosques built and restored during the reigns of Ubaydullah Khan, Abdulaziz Khan I, and Abdullah Khan II. Using the examples of the Kalyan Mosque, Khoja Kalon Mosque, the Khoja Zayniddin mosque-khanqah, the Volaidai Abdulaziz Khan Mosque, and the Shah Axsiy, Fayzobod, Namozgoh, and Kukaldosh mosques, the article elucidates the principal features of Shaybanid mosque architecture. In addition, on the basis of epigraphic sources, waqf documents, and written historical works, the article assesses the historical and cultural significance of these monuments and their place in the development of the Bukhara school of architecture.